2024
DOI: 10.1039/d3su00205e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chloride salts and microwaves on polyethylene terephthalate (PET) hydrolysis by iron chloride/acetic acid Lewis/Brønsted acidic deep eutectic solvent

Marco Rollo,
Massimo A. G. Perini,
Alessandro Sanzone
et al.

Abstract: Iron(iii)-based deep eutectic solvents were demonstrated to be active solvents for the hydrolysis of poly(ethylene terephthalate), especially under microwave irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…DESs based on hexa-hydrated FeCl 3 and acidic HBD were taken into account by Rollo et al [53], who found that the best HBDs were sulphonic acids, which were able to quantitatively transform PET into TA at 100 • C, with high recovery percentages. In a very recent work by the same group [54], the same iron salt was coupled to acetic acid in a proof-of-principle microwave-based experiment where the yield of TA monomer was raised from 4% to 54% by a sodium hydroxide post-treatment. Rather successful results were obtained also with the aid of less conventional reaction schemes that encompass depolymerization steps through microwave-assisted reactors, as reported in several works by Azeem and coworkers, who were able to degrade PET to TA, monohydroxyethyl terephthalate (MHET) and BHET using a series of sequential depolymerization processes in EG-choline chloride-(thio)urea DESs mixtures (glycolysis) followed by a treatment with sodium carbonate in EG (hydrolysis) [55].…”
Section: Introductionmentioning
confidence: 99%
“…DESs based on hexa-hydrated FeCl 3 and acidic HBD were taken into account by Rollo et al [53], who found that the best HBDs were sulphonic acids, which were able to quantitatively transform PET into TA at 100 • C, with high recovery percentages. In a very recent work by the same group [54], the same iron salt was coupled to acetic acid in a proof-of-principle microwave-based experiment where the yield of TA monomer was raised from 4% to 54% by a sodium hydroxide post-treatment. Rather successful results were obtained also with the aid of less conventional reaction schemes that encompass depolymerization steps through microwave-assisted reactors, as reported in several works by Azeem and coworkers, who were able to degrade PET to TA, monohydroxyethyl terephthalate (MHET) and BHET using a series of sequential depolymerization processes in EG-choline chloride-(thio)urea DESs mixtures (glycolysis) followed by a treatment with sodium carbonate in EG (hydrolysis) [55].…”
Section: Introductionmentioning
confidence: 99%
“…In view of all these applications, the preparation of new Zn(II)-based DESs and their in-depth characterization proves to be a topic of recognized interest. This class of DESs presents the additional advantage of the possible synergy between Lewis and Brønsted acids (LBDES), which has been already assessed in a few cases [28,33,[37][38][39][40][41][42][43], and more potential applications will be explored in the future. As is evident from some of these references, in some cases, the zinc-based solvent is catalytically active, meaning that one of the components of the DES directly enters into the mechanism of the reaction, lowering its activation barrier.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the DES preparation was performed without the elimination of water traces from the precursors, to reproduce the conditions required for their application. In fact, for interesting applications, such as PET [37,42] or cellulose [45] hydrolysis, at least a small amount of water has to be present in the system. Overall, this study represents a necessary starting point for future applications of these systems in different fields.…”
Section: Introductionmentioning
confidence: 99%